2020
DOI: 10.1016/j.marenvres.2020.104888
|View full text |Cite
|
Sign up to set email alerts
|

Electric and magnetic senses in marine animals, and potential behavioral effects of electromagnetic surveys

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 115 publications
2
27
0
1
Order By: Relevance
“…No se descarta la acción o influencia directa de la variabilidad del medio electromagnético natural en la reproducción, la fertilidad, el estrés y otros parámetros puramente biológicos de los crustáceos bajo estudio ya que se han encontrado numerosas evidencias de que numerosos objetos vivos reaccionan sensiblemente a los cambios electromagnéticos del medio en que viven, sobre todo a las frecuencias muy bajas (Nyqvist D. et al 2020;Litovitz et al 1992;Gmitrov y Ohkubo 2002;Kumosani y Qari 2003).…”
Section: Discussionunclassified
“…No se descarta la acción o influencia directa de la variabilidad del medio electromagnético natural en la reproducción, la fertilidad, el estrés y otros parámetros puramente biológicos de los crustáceos bajo estudio ya que se han encontrado numerosas evidencias de que numerosos objetos vivos reaccionan sensiblemente a los cambios electromagnéticos del medio en que viven, sobre todo a las frecuencias muy bajas (Nyqvist D. et al 2020;Litovitz et al 1992;Gmitrov y Ohkubo 2002;Kumosani y Qari 2003).…”
Section: Discussionunclassified
“…This was, however, a highly questionable practice, as was pointed out by both the industry and the scientific community. A literature study was initiated and the results indicated that the main EM disturbances to fish species are likely to occur during their navigation during migration [43]. In accordance with the general goal of the recommendations: to prevent recruitment failure, the migration towards spawning grounds was considered to be most important to protect.…”
Section: Onwards; New Technical Achievements Require New Advicementioning
confidence: 99%
“…Timeline is indicative and not to scale. The numbers in the bottom corner refer to publications given in the reference list; [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Seeing how well these animals are navigating, the question emerged which sensory information the seals and other marine mammals use for orientation and navigation. Theoretical speculation sprouted over the use of stars or the Earth's magnetic field [6][7][8]; while the first is based on good preliminary experimental evidence [9,10], magnetoreception has not been documented for seals [11]. In general, previous experiments regarding orientation and navigation in seals almost exclusively focused on cues perceived by the classic sensory systems, such as visual, auditory, chemoreceptive or hydrodynamic cues [12][13][14].…”
Section: Introductionmentioning
confidence: 99%